2019
DOI: 10.1002/2050-7038.12131
|View full text |Cite
|
Sign up to set email alerts
|

Reliability‐constrained optimal design of multicarrier microgrid

Abstract: Summary The unprecedented penetration of distributed generation in distribution energy networks provides utilities with a unique opportunity to manage portions of networks as microgrids (MGs). The implementation of an MG may offer many benefits, such as capital investments deferral, reduction of greenhouse gas emissions, improvement in reliability, and reduction in network losses. Future energy networks will contain various forms of energy which are acquired by mixing several sources and energy storages in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…Simultaneously, the enhancement of the power system reliability is achieved due to the obtained optimal BSS size and location. The reliability improvement and reduction in network losses are also observed using compound co-optimization strategic plan [23]. The reliability indices such as expected ENS, EIR, LOLE, and LOLP, are defined in the co-optimization strategy.…”
Section: Literature Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, the enhancement of the power system reliability is achieved due to the obtained optimal BSS size and location. The reliability improvement and reduction in network losses are also observed using compound co-optimization strategic plan [23]. The reliability indices such as expected ENS, EIR, LOLE, and LOLP, are defined in the co-optimization strategy.…”
Section: Literature Surveymentioning
confidence: 99%
“…To fulfill the RA in EDS [15], has introduced a restoration strategy for ENS calculation. The optimization of reliability indices has been considered in [20,23], and the improvement in the system's reliability is observed.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results showed that MO-CSA found well-distributed and widely spread non-dominated solutions in the Pareto front. Amir et al 20 presented a co-optimization method based on the mixed integer nonlinear programming and GA to find best size and of components of microgrid. Different reliability indices were considered in solving the optimization problem.…”
Section: Literature Survey and Contributionmentioning
confidence: 99%
“…Supply-demand equality constraint mentioned in Equation 14is expressed using Equation (27). The C s , H s , U s , and V s matrices in the compact matrix form express the matrices in Equations (16), (18), (19), (20), and (21) of the optimization problem described Section 3. The vector d s in Equation (27) represents the demand expressed in Equation (22).…”
Section: Compact Matrix Formmentioning
confidence: 99%